Clinical Profile and Health Disparities in a Multiethnic Cohort of Patients With Hypertrophic Cardiomyopathy. (17th March 2021) - Butters, Alexandra; Semsarian, Caitlin R.; Bagnall, Richard D.; Yeates, Laura; Stafford, Fergus; Burns, Charlotte; Semsarian, Christopher; Ingles, Jodie
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Clinical studies of hypertrophic cardiomyopathy are over-represented by individuals of European ethnicity, with less known about other ethnic groups. We investigated differences between patients in a multiethnic Australian hypertrophic cardiomyopathy population. Methods: We performed a retrospective cohort study of 836 unrelated hypertrophic cardiomyopathy probands attending a specialized clinic between 2002 and 2020. Major ethnic groups were European (n=611), East Asian (n=75), South Asian (n=58), and Middle Eastern and North African (n=68). The minor ethnicity groups were Oceanian (n=9), People of the Americas (n=7), and African (n=8). One-way ANOVA with Dunnett post hoc test and Bonferroni adjustment were performed. Results: Mean age of the major ethnic groups was 54.9±16.9 years, and 527 (65%) were male. Using the European group as the control, East Asian patients had a lower body mass index (29 versus 25 kg/m 2, P <0.0001). South Asians had a lower prevalence of atrial fibrillation (10% versus 31%, P =0.024). East Asians were more likely to have apical hypertrophy (23% versus 6%, P <0.0001) and Middle Eastern and North African patients more likely to present with left ventricular outflow tract obstruction (46% versus 34%, P =0.0003). East Asians were less likely to undergo genetic testing (55% versus 85%, P <0.0001) or have an implantable cardioverter-defibrillator implanted (19% versus 36%, P =0.037). East Asians were more likely to have a causative variant in a gene other than MYBPC3 or MYH7, whereas Middle Eastern and North African and South Asians had the highest rates of variants of uncertain significance (27% and 21%, P <0.0001). Conclusions: There are few clinical differences based on ethnicity, but importantly, we identify health disparities relating to access to genetic testing and implantable cardioverter-defibrillator use. Unless addressed, these gaps will likely widen as we move towards precision-medicine–based care of individuals with hypertrophic cardiomyopathy.